Fanfiction as ‘Textual Poaching’: Reconfiguring Fanfiction in Literary Production and Participatory Culture - Listya Ayu Saraswati (Bina Nusantara University, 2026)
This philosophical reflective paper examines the legitimacy and cultural value of fanfiction within contemporary literary discourse, questioning its position in relation to the established literary canon. Beginning with an exploration of the practices of reading and writing fanfiction as forms of ‘labor’ within fandom, the study acknowledges the skepticism and dismissal that often surround its worth. These practices open broader inquiries into how value, legitimacy, and participation are determined in literature. Drawing on Frank Raymond Leavis and Andrew Milner’s theories of the literary canon, Raymond Williams’s Cultural Studies, and Henry Jenkins’s concept of participatory culture, the paper reflects on the historical role of institutional gatekeeping in canon literature, where certain texts were privileged as morally and culturally superior while others were excluded. In contrast, fanfiction emerges as a democratized form of literary production, enabling diverse voices to reconfigure familiar narratives, subvert dominant ideologies, and address social issues overlooked in mainstream literature. Through a qualitative approach that combines close reading and extensive library research, this paper highlights fanfiction’s intertextual and transformative qualities, emphasizing its capacity to generate community, nurture identity, and foster critical literacy. Rather than dismissing fanfiction as marginal or derivative, the analysis demonstrates how it destabilizes hierarchical notions of literary value, revealing literature itself as a dynamic cultural practice rather than a fixed canon. This study argues for recognizing fanfiction as a vital form of contemporary storytelling and cultural labor, one that challenges conventional boundaries of legitimacy in literary criticism and reimagines the possibilities of cultural participation.